Progress towards a demonstration of multi-pulse laser wakefield acceleration and implementation of a single-shot wakefield diagnostic - Dann, S (2015)
An ongoing experiment is described to demonstrate the principle of multi-pulse laser wakefield acceleration, in which a plasma wakefield is resonantly excited by a train of laser pulses, spaced by the plasma wavelength. Particle-in-cell simulations of the initial single-pulse experimental setup are presented, in order to calculate the expected signal. Preliminary results are presented and future plans, based on work done so far, are discussed. Part of this work involves the implementation of a single-shot wakefield diagnostic — frequency-domain holography, which records the phase shift caused by passage of a probe pulse through the plasma. This implementation is described in detail, along with the associated analysis procedure. Practical difficulties encountered while implementing the diagnostic are discussed, along with possible ways of mitigating them in the future. A method is presented by which the noise level in the resulting phase measurements can be predicted, much more accurately than any previously published method for this technique. Methods of generating pulse trains for use in future multi-pulse laser wakefield acceleration experiments are presented. These include techniques proposed for use in this demonstration experiment, as well as one intended for use in a dedicated high-efficiency, high repetition-rate, multi-pulse driver laser. This last method, based on programmable pulse shaping using a spatial light modulator, requires a suitable mask to be computed based on the parameters of the required pulse train; an algorithm is described to perform this computation.